Leadership and Organizational Culture in Shaping the Success of Digital Transformation - Isra Muksin (TechTalent & Business Review, 2026)
Digital transformation is a strategic agenda for organizations, but its implementation often fails because it focuses too much on technology and neglects the role of leadership and organizational culture. This study aims to analyze the role of leadership and organizational culture in shaping the success of digital transformation. The study uses a qualitative approach with a case study design, where data is collected through in-depth interviews, observations, and document analysis of informants selected purposively based on their direct involvement in the digital transformation process. Data analysis is conducted thematically through the stages of reduction, presentation, and conclusion drawing. The results of the study indicate that leadership plays a role as a visionary, strategic decision maker, and role model in the application of digital work values, while also serving to strengthen an adaptive, collaborative, and innovative organizational culture. The success of digital transformation is marked by changes in work methods and business processes, increased collaboration and efficiency, and changes in mindset and digital-based work behavior. The findings also reveal that a lack of synergy between leadership and organizational culture causes digital transformation to be partial and unsustainable. This study confirms that the success of digital transformation is multidimensional and is the result of synergy between leadership and organizational culture, thereby contributing theoretically to the strengthening of non-technological approaches in the study of digital transformation and providing practical implications for organizations in designing sustainable digital transformation strategies.